Food from thought - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
- a series of narratives on the practical application of research conducted by the International CropsResearch Institute for the Semi-Arid Tropics (ICRISAT) and its collaborators. Issue number 3 is entitled: Improving theunimprovable - succeeding...